Australian business statistics - Selvanathan, E. Antony, 1954- (South Melbourne : Thomson, 2004)
Australian business statistics
Includes bibliographical references and index.
Previous ed.: Nelson Thomson Learning, 2000.
Computer disc in pocket inside back cover.
Keywords: Management -- Statistical methods -- Textbooks; Commercial statistics -- Textbooks; Economics -- Statistical methods -- Textbooks